FORMULATION AND EVALUATION OF CEFIXIME TRIHYDRATE TOPICAL GEL FOR WOUND INFECTIONS - Srinivasan, Uma Shankar Marakanam; Vishnu, Vishnu; Sharmila, Sharmila; Kumar, Amod (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this research work was to formulate and evaluate topical gel loaded with cefixime trihydrate, a third-generation cephalosporin antibiotic for the treatment of bacterial wound infections. Methods: The cefixime trihydrate gel was formulated using polymers such as Carbopol 940 and hydroxypropyl methylcellulose E4M in varying concentrations. Three different formulations were prepared and characterized physically for color, syneresis, spreadability, pH, drug content, and rheological properties. In vitro drug release in phosphate buffer pH 7.4 and antibacterial study were performed for the gel formulation to evaluate its therapeutic effect on wound infections. Results: The study demonstrated that the gel formulations showed promising results on their physical evaluation tests. The rheology behavior of the gel was shear-thinning flow type which indicated easy spreading of the gel. The drug release of the gel formulation F2 was selected as the best due to its highest drug release rate of 32.2% in comparison with the other two formulations after 2 h of the study. F2 formulation possessed the highest antibacterial activity as compared to other two formulations. Conclusion: A pioneering work was done on formulating cefixime trihydrate as a gel for topical administration. The antibacterial effect of the drug as gel formulation showed promising effect. We conclude that the cefixime trihydrate could be successively loaded into a gel formulation and can be used for effectively for wound infections like diabetic foot wounds.